Biochemical and Oral Biological Determinants of Tooth Movement Speed in Corticotomy-Assisted Orthodontics: A Clinical Study - Ayesha Yasir, Faryal Ali Syed, Junaid Israr Ahmed Khan, M. Shakil Zari Khawri Siddiqui, Mamoona Shuja, Usman Mahmood (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Corticotomy-assisted orthodontics accelerates tooth movement by stimulating regional acceleratory phenomena, yet the biological factors contributing to patient-specific variations remain insufficiently understood. Identifying the biochemical and oral biological determinants influencing movement speed may enhance predictability and individualized treatment planning. Objective: To evaluate the association of salivary biochemical markers and oral biological characteristics with the rate of tooth movement in patients undergoing corticotomy-assisted orthodontics. Methods: A prospective multi-center clinical study was conducted from January 2022 to May 2023 across Margalla Institute of Health Sciences (Rawalpindi), Baqai Dental College (Karachi), and the Department of Science of Dental Materials at Lahore Medical and Dental College (Lahore). A total of 130 orthodontic patients requiring maxillary canine retraction were included. Corticotomy was performed on one side while the contralateral side served as control. Tooth movement was recorded at baseline, week 1, week 4, and week 8. Salivary prostaglandin E2 (PGE2), interleukin-1β (IL-1β), alkaline phosphatase (ALP), tartrate-resistant acid phosphatase (TRAP), and matrix metalloproteinase-8 (MMP-8) were analyzed. Bone density, periodontal ligament width, and gingival phenotype were documented. Statistical analysis included paired t-tests, Pearson correlations, and multivariate regression. Results: The corticotomy side demonstrated significantly greater movement at all time points, with the highest displacement at week 8 (2.47 ± 0.31 mm vs. 1.15 ± 0.20 mm; p < 0.001). Salivary biomarkers were markedly elevated after corticotomy, particularly at week 4 (PGE2: 249 ± 33 pg/mL vs. 158 ± 28 pg/mL; IL-1β: 138 ± 20 pg/mL vs. 90 ± 14 pg/mL; p < 0.001). Strong positive correlations were observed between movement speed and PGE2 (r = 0.81), IL-1β (r = 0.75), TRAP (r = 0.71), and ALP (r = 0.67). Bone density showed a significant negative correlation (r = –0.57). Regression analysis identified PGE2, IL-1β, and bone density as the strongest independent predictors (R² = 0.74). Conclusion: Biochemical inflammatory mediators and bone-turnover markers, along with baseline skeletal characteristics, strongly influence the rate of tooth movement in corticotomy-assisted orthodontics. Salivary biomarkers provide a practical, non-invasive method for predicting treatment response and guiding personalized orthodontic planning. Keywords: Corticotomy-assisted orthodontics, tooth movement speed, salivary biomarkers, PGE2, IL-1β, bone density, periodontal biology, orthodontic acceleration.